PENGARUH KEHALUSAN BAHAN DAN LAMA EKSTRAKSI TERHADAP MUTU EKSTRAK TEMULAWAK (Curcuma xanthorriza Roxb) - Bagem Br. Sembiring; Ma’mun Ma’mun; Edi Imanuel Ginting (Buletin Penelitian Tanaman Rempah dan Obat, 2006)
The Influence Of The Particle Size And Length Of Extraction On The Yield And Quality Of Curcuma Extract (Curcuma xanthoriza)The effect of suitable method condition to quality of Curcuma extract, was conducted in the Laboratory at Post Harvest Technology Labora-tory of Research Institute for Aromatic and Medi-cinal Crops Bogor from Mart to May 2006. The objective of this experiment to find out the suita-ble method condition to get quality Curcuma ex-stract. Randomized complete design with factorial was used and using 2 replications. The trearment divided 2 factors, they are material of particle size and duration of extraction. Two particles size inclu-ding 40 and 60 mesh, and three lengths of ex-traction including 4, 6 and 8 hours were tested. The result showed that the particle size influen-ced the extract yield, curcumin content, oil con-tent and xanthorizol content in the extract. Mean while, the length of extraction influenced the ex-tract and oil content. The highest Cur-cumin content is 2.88% obtained from 40 mesh particle size material, while Xanthorizol content is 14.25% obtained from material with 60 mesh of particle size.